Caracterización fenotípica y funcional de subpoblaciones de células mononucleares de sangre periférica de pacientes con inmunodeficiencias primarias que cursan con manifestaciones disregulatorias : asociación con alteraciones presentes - Caldirola, María Soledad (2019)
Primary immunodeficiencies (PID) are congenital diseases of heterogeneous clinical\npresentation. They represent disorders caused by mutations that affect the development and/or\nfunction of several compartments of the immune system, which predispose patients to\ninfections, autoimmunity, allergy and cancer. The study of peripheral blood mononuclear cell\nsubpopulations of patients with disregulatory syndromes due to mutations in CD25, STAT5b,\nSTAT1 and STAT3, allowed us to reveal the critical role of the IL-2/CD25/STAT5b axis in\nNK cell maturation and the regulation of antibody production regulated by follicular helper T\ncells (Tfh), the differentiation of naïve B cells into class switched B cells and plasma cells, the\ndysregulation of the germinal center (GC) and the production of autoantibodies. Accordingly,\nSTAT5b plays a fundamental role in humoral response and maintenance of immune system?s\ntolerance. In summary, using peripheral blood of patients with PIDs, we could elucidate new\nregulatory pathways in human immune system, confirming that these patients represent\n"natural models" that provide an excellent opportunity to elucidate mechanisms of the human\nimmune system that remain ill-defined.